Axiomatic Design Principles in Analysing the Ergonomics Design Parameter of a Virtual Environment - Zahari, Taha; Soewardi, Hartomo; Siti Zawiah, Md. Dawal (Elsevier, 2014)
One of the negative side effects experienced by users when interacting with virtual environment is visual symptoms. This paper explores the ergonomics design parameters of the virtual environment to minimize such negative side effect by applying axiomatic design principles. Axiomatic design is a method to provide a systematic way for designing products and large systems. The independence axiom is used to map customer domain (CAs) to functional domain (FRs) and physical domain (DPs). A paper based survey was conducted to identify and define customers' preference in the virtual environment. A virtual robot manufacturing system was developed as a case study to explore ergonomic design parameters that satisfy the independence of FRs and CAs. Results of this study shows that the ergonomic design parameters of virtual environment identified (DP161-DP162-DP121-DP111-DP131-DP141-DP151-DP152) have satisfied the independence functional requirement and desired visual comfort for users. By uncoupling the design it provides an efficient and effective sequence of design activities FR161-FR162-FR121-FR111-FR131-FR141-FR151-FR152.